Encouraging Community Empowerment and Local Economic In-dependence in Villages through Sustainable Economic Develop-ment Techniques - Nazeri, Nazeri; Hidayat, Rahmat; Maza, Rina El (Eastasouth Institute, 2024)
With an emphasis on local economic independence and community empowerment, this publication examines sustainable economic development tactics in villages. The purpose of this study is to present an integrated and comprehensive picture of sustainable village economic development. The researchers assessed economic development initiatives in several community areas in Indonesia, using qualitative descriptive methods. The study findings suggest that a comprehensive and integrated approach that considers the economic, social, cultural, and environmental demands of the local population is necessary for sustainable economic development in villages. To achieve local economic independence, community empowerment through active community involvement in the formulation and implementation of economic development programs is essential. The authors of this article suggest a sustainable economic development plan for villages that is based on the ideas of community empowerment and participation. Leveraging local resources, strengthening organizations and cooperatives, empowering women and youth, developing small and medium enterprises and the agricultural sector, and implementing sustainable environmental management are all part of this plan. In conclusion, a comprehensive and integrated approach that emphasizes local economic independence and community empowerment can lead to sustainable economic development in villages. Such a plan can improve the welfare of village communities and encourage sustainable economic growth.